Parallel Finite Volume Method Simulation of Three-Dimensional Fluid Flow and Convective Heat Transfer for Viscoplastic Non-Newtonian Fluids - Vasco-Calle, D (Taylor and Francis Ltd., 2014)
Three-dimensional fluid mechanics and heat transfer for viscoplastic flows are described by finite volume method, FVM. The open multi-processing approach has been implemented to parallelize the numerical code. Results for the elapsed times, speed-ups and efficiencies are presented. The code was used to describe the natural convection (Ra = 104; 106) and the lid-driven cavity (Re = 100; 1000) processes with Bingham, Casson and Herschel-Bulkley fluids (Bn = 0.01; 1.0). Results describing isotherms, velocity distributions and streamtraces, as a function of Ra, Re, Pr and Bn numbers are shown. The grid size analysis shows that different sizes are required to obtain precise results for Nusselt number and friction factor. © 2014 Copyright Taylor & Francis Group, LLC.